Turning History into a Fairy Tale: The Borders of Reality and Fiction in Catherynne Valente’s Deathless - Vinczeová, Barbora; Saduov, Ruslan T. (American & British Studies Annual, 2017)
This article explores the parallels between the classic Russian fairy tale Marya Morevna and its reimagining in Catherynne Valente’s Deathless. The authors claim that the novel follows the pattern of the postmodern reinterpretation of fairy tales and provide a thorough analysis of the characters, setting, style and other phenomena supporting this claim. The novel simultaneously addresses the themes of political and social criticism of early Soviet Russia, resulting in the ironic tone and satirical comments provided by the author. The literary analysis strives to answer the question ‘how is this fairy tale combined with history?’ The novel transcends the genre of a fairy tale retelling and functions as a novel filled with historical references and subjective commentary on the political and the social situation.